Analisis Dampak Instrumen Investasi Keuangan Syariah Sebagai Determinan Pertumbuhan Ekonomi Nasional Periode 2013-2020 - Saiful Muchlis; Munir; Rimi Gusliana Mais (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2022)
This study aims to analyze the effect of sharia shares, sukuk, and sharia mutual funds on national economic growth in 2013-2020. The research methodology used associative quantitative research using secondary data from sharia shares, sukuk, and sharia mutual funds data obtained from www.ojk.go.id. Meanwhile, data on national economic growth is obtained from www.bps.go.id. The results of this study are sharia stocks have a significant effect on national economic growth, sukuk have a significant effect on national economic growth and sharia mutual funds have no positive effect on national economic growth.